2023
DOI: 10.3389/fsufs.2023.1207197
|View full text |Cite|
|
Sign up to set email alerts
|

Optimizing water-energy-food nexus: achieving economic prosperity and environmental sustainability in agriculture

Andrianto Ansari,
Shafira Wuryandani,
Arin Pranesti
et al.

Abstract: The increasing global population, rapid urbanization, and climate change are putting unprecedented pressure on limited water and energy resources for food production. It requires integrated management of the key resources to achieve economic and environmental sustainability. The water-energy-food (WEF) nexus, in conjunction with circular bioeconomy (CBE) principles, offer a promising approach to achieve sustainable agriculture. It provides the integration between interconnectedness and interdependencies of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Studies have demonstrated that mangrove forests have higher carbon sequestration potential compared to other terrestrial ecosystems (Alongi, 2012;Hilmi et al, 2017;Hamilton and Friess, 2018).Therefore, the conservation of mangroves not only benefits the blue swimming crab fishery but also contributes to global efforts to combat climate change by preserving crucial carbon sinks. The interconnectedness of mangrove conservation, aquatic biodiversity, and the well-being of the blue swimming crab highlights the need for integrated coastal management practices to ensure the resilience and sustainability of these ecosystems (Johnston et al, 2021;Marine and Fisheries Ministry of Indonesia, 2022;Ansari et al, 2023b).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that mangrove forests have higher carbon sequestration potential compared to other terrestrial ecosystems (Alongi, 2012;Hilmi et al, 2017;Hamilton and Friess, 2018).Therefore, the conservation of mangroves not only benefits the blue swimming crab fishery but also contributes to global efforts to combat climate change by preserving crucial carbon sinks. The interconnectedness of mangrove conservation, aquatic biodiversity, and the well-being of the blue swimming crab highlights the need for integrated coastal management practices to ensure the resilience and sustainability of these ecosystems (Johnston et al, 2021;Marine and Fisheries Ministry of Indonesia, 2022;Ansari et al, 2023b).…”
Section: Discussionmentioning
confidence: 99%